Tax Risks in the Context of Digitalization of the Economy - Olga SINENKO; Igor MAYBUROV (Communications of International Proceedings, 2020)
The use of modern digital technologies in the process of tax administration not only opens up new opportunities, but also creates additional tax risks for the state and taxpayers. The article presents a study of tax risks under the conditions of the digitalization of the economy. The purpose of this study is to identify and systematize tax risks and to work out criteria for tax risk assessment in the context of digitalization. The study used the methods of logical and systems analysis of tax risks under the condition of the digitalization of the economy; content analysis was employed to analyze the available literature; the best practices of tax administration digitalization were summarized; the practice of using digital technologies to minimize tax risks was explored.
Keywords: Tax Risks; Digitalization; Risk-Based Approach; Tax Administration; Tax Risk Management; Digital Technology.